THEORETICAL BASIS AND PRACTICAL DIRECTIONS OF OPTIMIZATION OF FINANCIAL INSTRUMENTS AND INVESTMENT SOURCES IN FREE ECONOMIC ZONES (American Journal of Business Management, Economics and Banking, 2025)
This article provides a scientific analysis of the types of financial instruments and investment sources in free economic zones (FEZs), their economic efficiency and impact on regional development. The role of financial instrument diversification, preferential financing, infrastructure bonds, venture capital and digital grant platforms in FEZs is highlighted. Also, the institutional-pluralistic approach to the development of financial infrastructure, balancing resource asymmetry and vertically integrated financing models are evaluated from the point of view of efficiency. As a result of the analysis, theoretical conclusions and practical proposals have been developed to increase investment attractiveness, diversify risks and ensure financial stability in FEZs.